Preparation and Storage of High-Titer Lactic Streptococcus Bacteriophages - Nyiendo, J. (1974)
Various techniques were employed for preparation of high-titer bacteriophage lysates of Streptococcus lactis, S. cremoris, and S. diacetilactis strains. Infection of a 4-h host culture in litmus milk at 30 C yielded the highest titers (2 × 10(9) to 4 × 10(11) plaque-forming units/ml) for most phages. Host infection in lactose-containing broth produced similar virus numbers only when 0.1 M tris(hydroxymethyl)aminomethane buffer stabilized the pH. The pH at the time of infection as well as the inoculum phage titer were critical in obtaining high titers. Optimum conditions for infection in broth were coupled with a polyethylene glycol concentration procedure to routinely produce milligram quantities of phage from 1 liter of lysate. Neutralization of whey lysates, as a means of storage, offered no survival advantage over unneutralized samples. Storage of phage lysates in a 15% glycerol whey solution at -22 C yielded a high rate of survival in most cases, even with repeated freezing and thawing, over a period of 24 months.